Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1002/1097-4636(200010)52:1<58::aid-jbm8>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the genotoxicity of a naturally occurring crosslinking agent (genipin) for biologic tissue fixation

Abstract: The objective of the present study was to evaluate in vitro, using Chinese hamster ovary (CHO-K1) cells, the genotoxicity of genipin, a naturally occurring crosslinking agent. Glutaraldehyde, the most commonly used crosslinking agent for biologic tissue fixation, was employed as a reference chemical. The selected procedures for this evaluation were the micronucleus (MN) and sister chromatid exchange (SCE) assays with or without the addition of a metabolic activation system (S9 mix). Before starting the genotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 33 publications
1
120
0
4
Order By: Relevance
“…In agreement with previous studies demonstrating genipin biocompatibility (Tsai et al, 2000), we found that the crosslinked substrate could be used to generate bioengineered epidermis of similar thickness as control dermis. Mechanical measurements showed that crosslinking increased the dermal substrate stiffness by threefold.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous studies demonstrating genipin biocompatibility (Tsai et al, 2000), we found that the crosslinked substrate could be used to generate bioengineered epidermis of similar thickness as control dermis. Mechanical measurements showed that crosslinking increased the dermal substrate stiffness by threefold.…”
Section: Discussionsupporting
confidence: 92%
“…Crosslinkers such as glutaraldehyde have been used previously to increase the stability of natural polymer scaffolds in different tissue engineering applications; however, this practice has been postulated to have negative repercussions (in vitro and in vivo) in some cases, including geno/cytotoxicity and graft failure (Heydarkhan-Hagvall et al 2008;Tsai et al 2000). The blending of synthetic and natural polymers has been viewed as a non-toxic alternative to the use of chemical cross-linkers (Heydarkhan-Hagvall et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In reaction mechanism between gelatin and tannin are involved hydrogen bonds between hydroxyl groups of tannin and polar groups of gelatin, and hydrophobic interactions between pyrrolidine ring of Pro and pentagalloyl glucose from tannin (Obreque-Slier et al, 2010;Pena et al, 2010). Anti-inflammatory properties are added values during genipin-induced cross-linking, showing to be 10, 000 times less cytotoxic then glutaraldehide which may produce weakly clastogenic responces in CHO-K1 cells (Tsai et al, 2000;Sisson et al, 2009). Moreover, the minimal calcium content of genipin-fixed tissue was detected (Chang, 2001).…”
Section: Methodsmentioning
confidence: 99%